IMPLEMENTASI PROGRAM LAYANAN ADMINISTRASI KEPENDUDUKAN BERBASIS KEWENANGAN DESA DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN BANTAENG - Ismawati, Ismawati; Hakim, Lukman; Syukri, Syukri (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study purposed to determine the implementation of the village authority-based administrative service program based on program indicators, implementing organizations and target groups as well as supporting and inhibiting factors in its implementation at the Population and Civil Registration Office of Bantaeng Regency. This study used a qualitative descriptive type of research, to provide an overview of the implementation of village authority-based administrative services. The data analysis technique used data reduction, data presentation and conclusion. Then the data collection techniques used observation, interviews and documentation studies. The results of the study indicated that (a) the program, the village authority-based administrative service program had a clear objective, namely to make the administration of population administration closer, faster and the community no longer incured costs; (b) the implementing organization, the ability of the koordukcapil in providing population administration services in the village was good because it provided a quick response when there were people who took care of the authority-based administrative services; and (c) the target group were all village communities in Bantaeng Regency.